Lightweight hybrid composite b-pillars for automotive applications; Flexural performance evaluation - M. I., Ibrahim; Mohd Ruzaimi, Mat Rejab; Nasrul Azuan, Alang; M. F., Rani (IOP Publishing, 2025)
An automobile’s B-pillars are specifically intended to effectively absorb collision energy while minimizing deformation to ensure minimal intrusion into the vehicle’s interior. This study investigates the development of automotive B-pillars using different composite materials to enhance structural property and mechanical performance, aiming to reduce component weight as an alternative to traditional steel. Specifically three combinations of hybrid composite B-pillars were fabricated using 3 layers of carbon fibre as base material. The components were reinforced at the critical area with different and hybrid configurations: two aramid fibre interlayers, two glass fibre interlayers, and a hybrid patch comprising carbon and glass fibre layers. Fabrication process employed a conventional hand lay-up technique producing a full-size B-pillar of an A-segment vehicle. Weight reduction of the fabricated composite-based pillars is between 33% to 56% lighter than original steel pillar. Experimental three-point flexural tests with incorporation of strain gauges were conducted to evaluate flexural characteristics and strain responses. Results indicate that interlayer-reinforced composite pillars demonstrated superior flexural resistance compared to lightest patch-reinforced pillar, which exhibited lower energy absorption capabilities. The CGCGC configuration shows the greatest force resistance, with a peak force only 2% higher than the CACAC. Additionally, CGCGC withstands a 9% greater displacement before failure. Strain measurements confirm the observed load-displacement behaviours across all samples. The CGCGC hybrid B-pillar demonstrates significant potential for future applications, offering a 43% weight reduction and a 50% increase in energy absorption. This research highlights the viability of composite materials, particularly those utilizing interlayer hybrids, as robust and lightweight alternatives to steel for automotive B-pillar applications.